2007
DOI: 10.1002/pmic.200600313
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of lipid oxidation‐induced oxidation of porcine and bovine oxymyoglobins

Abstract: Myoglobin (Mb) redox state affects meat color and is destabilized by lipid oxidation products such as 4-hydroxy-2-nonenal (HNE). Our objective was to investigate lipid oxidation-induced oxymyoglobin (OxyMb) oxidation in Mb from two major meat-producing livestock species utilizing MS and proteomics tools. Porcine OxyMb was incubated with HNE and analyzed for metmyoglobin (MetMb) formation. MetMb formation was greater in the presence of HNE than controls at pH 7.4 and 37 degrees C (p <0.05). MALDI-TOF MS was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 89 publications
8
109
0
5
Order By: Relevance
“…Marcinek et al (2001) reported that the oxygen binding depends on the amino acid sequence surrounding the heme pocket. In addition, the primary amino acid sequence can affect the tertiary structure, which in turn can influence interaction with ligands and also the volume of the heme cavity (Suman et al, 2007). In support, Bunn (1971) reported that porcine hemoglobin has greater oxygen affinity than bovine hemoglobin, due to differences in amino acid composition.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Marcinek et al (2001) reported that the oxygen binding depends on the amino acid sequence surrounding the heme pocket. In addition, the primary amino acid sequence can affect the tertiary structure, which in turn can influence interaction with ligands and also the volume of the heme cavity (Suman et al, 2007). In support, Bunn (1971) reported that porcine hemoglobin has greater oxygen affinity than bovine hemoglobin, due to differences in amino acid composition.…”
Section: Discussionmentioning
confidence: 74%
“…In support, Bunn (1971) reported that porcine hemoglobin has greater oxygen affinity than bovine hemoglobin, due to differences in amino acid composition. Furthermore, variation in the primary structure was responsible for species-specific effects of secondary lipid oxidation products on myoglobin redox stability (Suman et al, 2007). For example, porcine myoglobin contains 9 histidine residues, while bovine myoglobin contains 13 residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian O 2 (II)Mb can be oxidized by copper ions with a dependence on binding of the metal to histidine residues in a species (pig, sperm whale, and horse)-specific manner (44). The lipid oxidation product, 4-hydroxy-2-nonenal (HNE), binds to His 24, 36, and 119 in pig Mb and His 24, 36, 81, 88, 93, 119, and 152 in bovine Mb (71). HNE binding to Mb has been shown to accelerate Mb oxidation.…”
Section: Reactions Of Mb With Other Biomoleculesmentioning
confidence: 99%
“…The mechanism responsible for Mb aggregation has been partly characterized; Mb itself tends to self-aggregate (Chow et al, 1989), whereas it has been reported that, in postmortem meat, Mb binds to myofibrillar proteins (Chajian et al, 2008) or reacts with fatty acids (Suman et al, 2007).…”
Section: Resultsmentioning
confidence: 99%